Adsorption of Lead (Pb2+) Using Biochar Derived from Bamboo Waste Pyrolysis - Ilham Mufandi; Muhammad Nur Kholis; Mahmudah Hamawi; Much Taufik Ardani; Hafidha Ayu Kusuma (Jurnal Ilmu Lingkungan, 2025)
The increasing of industrial activities and urbanization have led to the accumulation of heavy metals, which pose a high risk to human health and ecosystems. Adsorption using biochar from bamboo waste is an alternative solution as an adsorbent. This study evaluated the performance of biochar from pyrolysis of bamboo waste at various temperatures (300–600°C) for adsorption of lead (Pb²⁺) ions. The pyrolysis was conducted under a nitrogen gas atmosphere to prevent oxidation during thermal decomposition. Fourier Transform Infrared (FTIR) analysis revealed an increase in the stability of carbonyl (C=O) and carbon–nitrogen (C–N) functional groups with increasing temperature, which contributed to a stronger affinity for metal ions. Brunauer–Emmett–Teller (BET) analysis showed that biochar produced at 400 °C exhibited the most favorable surface characteristics, with a surface area of 178.56 m²/g, a pore volume of 0.091 cm³/g, and an average pore diameter of 2.05 nm. This sample also demonstrated the highest Pb²⁺ adsorption capacity of 52.4 mg/g. Despite higher porosity, the biochar produced at 600 °C showed diminished adsorption efficiency due to pore structure collapse and decreased carbon content. The findings suggest that biochar synthesized at 400 °C has strong potential for use in environmental remediation applications, particularly in mitigating lead contamination in water systems.